Implementasi Manajemen Pengetahuan dan Dampaknya terhadap Kinerja Organisasi pada PT Telekomunikasi Indonesia, Tbk - Andria, Veby; Trisyulianti, Erlin (Jurnal Manajemen dan Organisasi, 2011)
Economic growth towards globalization that indicated with rapid growth in information technology and communication technology brings impact to human resources development or knowledge based worker to support each organization activity. On the other side, globalization has changed world business community’s opinion to be knowledge society and took along the impact to growth of knowledge based competition. PT Telekomunikasi Indonesia, Tbk has applied knowledge management. PTTelekomunikasi Indonesia, Tbk is also one of the company who applied knowledge management well. It can be proved that the company has achieved reward MAKE (Most Admired Knowledge Enterprises) by an consultant organization, Dunamis (the seizer’s license). The objectives of this research are (1) To explain the model of knowledge management and organization performance at PT Telekomunikasi Indonesia, Tbk, (2) To explain the managerial implication for PT Telekomunikasi Indonesia, Tbk about knowledge management, (3) To explain employee’s perception about realization of knowledge management, (4) To explain organization performance before and after knowledge management applied, (5) To explain the obstacles in implementation of knowledge management and solutions alternative of the impact of knowledge management for increasing organization performance. This research was done at PT Telekomunikasi Indonesia, Tbk. This research uses descriptive analysis and Structural Equation Modelling (SEM), which has a goal to examine between construct independent and dependen also relation between laten variable indicators. The result of this research indicates that organization performance is influenced by knowledge management. The point of contruct coefficient ( ) is 0,62 and t-value 4,22. This point indicates that knowledge management is real significantly and positively influences organization performance. Level of knowledge management implementation is higher shows that level of organization performance is higher too. The impact of knowledge management TELKOM can be shown by product inovation FlexiCombo. Besides that, employee’s compentency development can be done by knowledge access through technology. Employee can access it by offline or online so that time efficiency can be attainable.